LEGAL PROTECTION AGAINST CHILDREN OF CRIMINAL OFFENSES THROUGH THE IMPLEMENTATION OF DIVERSION IN INDONESIA - RAHMAT, DIDING (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
This research aims to analyze the application of diversion as a legal protection measure for children involved in criminal acts. Diversion is an alternative case resolution process that aims to avoid negative stigma and punishment that can harm a child's development. The research method used is normative juridical, by examining statutory regulations, official documents and related literature. The research results show that the implementation of diversion in Indonesia“has been regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which provides guidelines for law enforcement officers in implementing diversion. In addition, legal protection for children who commit criminal acts”through the implementation of diversion provides an opportunity for children to receive more humane treatment, safeguards children's rights, and encourages community participation in the resolution process. Thus, it is hoped that the implementation of diversion can provide restorative justice and reduce the possibility of children repeatedly violating the law.